Robust non-linear control of a hybrid water pumping system based on induction motor - Zakaria Massaq; Abdelouahed Abounada; Mohamed Ramzi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This contribution presents a non-linear control of a hybrid pumping system supplied with a photovoltaic generator and a battery. This system is employed for delivering a continuous volume of water whatever the climatic conditions. In the DC side, a boost converter is controlled with the indirect double integral sliding mode controller (DISMC) for maximum power point tracking (MPPT). The DISMC is suitable for MPPT because it gives a fast response and reduces the amplitude of power oscillations. Then, a bidirectional buck-boost converter is adopted to ensure the energy management between the battery and the DC-bus, and this converter is controlled with integral sliding mode control (ISMC) theory.  The non-linear predictive control (NPC) is chosen to drive an induction motor (IM), the NPC is known by its fast dynamic and high capacity to reject disturbances. The hybrid system is modelled in MATLAB/Simulink software. During simulations, the DISMC-MPPT is compared with other techniques such as sliding mode controller (SMC) MPPT and integral SMC MPPT, the DISMC provides the best tracking performances under different irradiances. Moreover, the designed controller for the bidirectional converter regulates the DC-link voltage with better performances than the classical PI controller. Lastly, the NPC regulates the speed of the IM with high robustness.